Peran Perencanaan Pemasaran Terhadap Penjualan di Rumah Makan Payakumbuah - Mohammad Makhrisyafrisal; Ummi Istiqomah; Didik Sapto Raharjo; Danang Aziz Akbarona (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The increased degree of competition in the post-Covid-19 culinary industry has forced business owners, particularly Rumah Makan Padang Payakumbuah, to implement efficient marketing techniques aimed at increasing sales and ensuring long-term economic viability.  This study addresses the primary topic of how well-planned marketing strategies can improve the sales performance of culinary businesses in a quickly changing market environment.  The major goal is to investigate and evaluate the marketing planning strategies used and their influence on business growth.  This study employs a literature review strategy in conjunction with a qualitative descriptive methodology.  Content analysis is used to investigate relevant sources, such as academic journals, scholarly books, articles, and other secondary data that support the study's findings. According to the findings, Rumah Makan Padang Payakumbuah has successfully developed a comprehensive marketing strategy using digital technologies such as social media platforms, search engine optimization (SEO), and innovative, theme-based promotional campaigns. Such attempts have been successful in raising brand awareness, expanding market reach, and dramatically increasing sales volume. Furthermore, the integration of the marketing mix (4Ps) and SWOT analysis has improved the company's competitive position in an increasingly saturated businesses.  The emphasis on authentic culinary flavors, precise market segmentation, and a digitally driven promotional approach are identified as key drivers behind the business’s notable success.